Anti-Candida activity of beneficial vaginal lactobacilli in in vitro assays and in a murine experimental model. Issue 2 (24th January 2019) - De Gregorio, Priscilla Romina; Silva, Jessica Alejandra; Marchesi, Antonella; Nader-Macías, María Elena Fátima
ABSTRACT: Vulvovaginal candidiasis (VVC) is one of the most frequent infections affecting women worldwide. Healthy vaginal microbiota is dominated by lactobacilli, which form a strong defense line against pathogens. In this work, in vitro antimicrobial properties of thirty vaginal Lactobacillus strains were evaluated against eleven Candida vaginal clinical isolates, employing three different methods. Also, the effect of intravaginal (i.va.) administrations (preventive, therapeutic and preventive-therapeutic) of L. reuteri CRL1324 or L. rhamnosus CRL1332 strains against the i.va. challenge with Candida albicans C2 (C.a.) was evaluated in a murine experimental model. From the results of agar overlay and liquid medium assays the selected lactobacilli strains have shown to inhibit the growth of at least one Candida strain. The inhibition was mainly due to the effect of organic acids. Anti- Candida activity was not evidenced in the agar plate diffusion method. In the experimental murine model, only preventive-therapeutic administration of both lactobacilli was able to significantly reduce viable C.a. numbers recovered in vaginal washes and the leukocyte influx induced by the fungi. In conclusion, lactobacilli exhibited in vitro and in vivo antimicrobial effects on Candida, suggesting that they could be promising candidates for protection against VVC. Abstract : Lactobacilli predominant in human vagina and protect from vulvovaginal candidiasis. The manuscript reports different methods to determine lactobacilli inhibitory effect at the laboratory, and protection against Candida in murine vagina.